Bacterial removal in flattened root canals with different tapers of ProDesign Logic single-file system (Research, Society and Development, 2021)
Objective: This study evaluated the bacterial removal in flattened root canals after preparation with different tapers of ProDesign Logic instruments. Methodology: Fifty-five mandibular incisors with flattened root canals were contaminated with a pure culture of Enterococcus faecalis ATCC 29212 for 21 days at 37ºC. Root canals preparation was performed using ProDesign Logic and 0.9% sterile saline solution for irrigation. The specimens were randomly allocated to three experimental groups (n = 15) according to the taper of the instrument used: 25.03, 25.04, or 25.06. Intracanal bacteriological samples were taken before (S1) and after (S2) preparation and the number of colony-forming units per milliliter (CFU/mL) was calculated. Differences in bacterial counts before and after treatment, within each group, were analyzed by the paired t-test. Groups were compared by ANOVA with a post hoc test. The level of significance was set at p